Tecnologia, poder e violência em 2001 : uma odisseia no espaço - Failache, Mauricio José Vera (Universidade Federal de São Carlos, 2015)
The present work undertakes the film analysis of the feature film 2001: A Space Odissey (1968) of Stanley Kubrick, in wich the origin of the tool is associated with the origin and transformation of man throughout history. The Discovery and use of the tool provided a new knowledge and, along with it, a number of effects permeated by Power relations –analyzed based on diverse authors point of view, between them Michel Foucault. The literary-cinematographic genre to wich 2001: A Space Odissey belongs to, is science fiction, wich is the natural medium to social, political, economic and even religious criticism. Kubrick with this film within the sixties context, opens a new era in major productions of the genre, wich had been relied on a few technological and economic resources, and also for its high aesthetic quality both at photographic level and special effects. The narrative style is no less innovative because in a genre where everything was explained in detail, Kubrick shows a visual story, to be told through different musics and images, and not just relied on dialogs and callouts. This paper also notes the relationship between humans and their Technologies represented in the film, from the issue of the otherness as conceived by Bakhtin.
Keywords: Análise do discurso; Análise fílmica; Cinema; Kubrick, Stanley, 1928-1999; Ciência, tecnologia e sociedade; Film analysis; Stanley Kubrick; Power; Knowledge; Technology; Society; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::TEORIA DA INFORMACAO; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA